The Influence of Perinatal Education on Breastfeeding Decision and Duration - Zugravu, Corina; Nanu, Michaela Iuliana; Moldovanu, Florentina; Arghir, Oana Cristina; Mihai, Cristina Maria; Oțelea, Marina Ruxandra; Cambrea, Simona Claudia (International Journal of Child Health and Nutrition, 2018)
Objectives: to evaluate factors influencing breastfeeding duration in an integrative model, considering both the organization of medical care and the perinatal education. Methods: We conducted a cross sectional study with data collected in a face to face interview of 1,008 mothers with children aged between 9 and 14 months The questionnaire focused on the main characteristics of a Mother-Baby Friendly Hospital initiative and the type of perinatal education received by pregnant women. Correlation and partial correlation tests, non-parametric tests and classification tests were applied. Data were processed in SPSS 12.0 software. Results: The positive effects of Mother Baby Friendly Hospitals Organization initiative organization were confirmed. However, the main differentiator for breastfeeding duration was the level of formal education of pregnant mothers and the active seeking of perinatal education (r = 0.22, p< 0.001). The perinatal counseling was correlated with breastfeeding duration only for the subgroup participating to structured, dedicated time slot apart from the regular medical consultation (r = 0.079; p = 0.014), independently of mother’s age, education, residence, time to first breastfeeding contact, type of birth delivery and rooming in. Our results support a broader approach to perinatal education than medical counseling during pregnancy to increase the voluntary participation of future mothers to the perinatal educational programs. Conclusion: As mothers’ motivation to maintain the optimum duration of breastfeeding is a determinant factor, an earlier and sustained educational process, before pregnancy and after birth delivery, is necessary in order to create a general favorability for exclusive breastfeeding.